Emerging therapies for triple-negative breast cancer. (January 2013) - Anders, Carey K; Carey, Lisa A
SUMMARY Triple-negative breast cancer (TNBC) lacks expression of the estrogen, progesterone and HER2 receptors and is a clinical problem representing 15–20% of diagnosed breast cancers. TNBC is over-represented among premenopausal, African–American women and among women with incurable disease. Tremendous efforts in the preclinical and clinical setting are dedicated to developing more effective, targeted agents to treat this aggressive disease. Promising therapies, including inhibitors of the EGF receptor, VEGF receptor and PARP, have not had the desired success, potentially due to heterogeneity within TNBC. Ongoing preclinical work is focused on inhibition of Chk1, HDAC and the PI3K and/or mTOR pathways.